Analysis of Human Resources Competence in State Asset Management (BMN) Through Siman and Sakti Applications Based on Technology Accepted Model (TAM) at KPKNL Kisaran - Loven Xaverius Simamora; Hendrian; Shine Pintor Siolemba Patiro (Universitas KH. Abdul Chalim Mojokerto, 2025)
The importance of human resource capabilities in managing state assets effectively and accountably through digital systems, along with the technological transformation in the state financial management bureaucracy. Although the implementation of the SIMAN and SAKTI applications has been ongoing, variations in the level of competence and user acceptance still impact the effectiveness of BMN management. This study aims to analyze the competence of human resources (HR) in managing State Assets (BMN) through the SIMAN and SAKTI applications using the Technology Acceptance Model (TAM) approach. The method used in this study is qualitative; the analysis is carried out based on the Technology Acceptance Model (TAM) framework that assesses the perception of ease of use (perceived ease of use), perception of usefulness (perceived usefulness), and acceptance of technology to improve HR competency. The results of the study indicate that the HR of the Kisaran KPKNL has a fairly good level of competence in using the SIMAN and SAKTI applications to implement BMN management, especially the process of inputting and reporting state assets. HR competence and technology acceptance are key elements in the success of the digital transformation of BMN management. Improving digital competency through adaptive training, organizational support, and strengthening individual motivation are strategic steps to support transparent, efficient, and accountable governance of state assets in the digital era.